Effect of Credit Risk, Market Risk and Liquidity Risk on Return On Assets of Conventional Commercial Banks Registered in the Financial Services Authority During the COVID-19 Pandemic - Esha Pratiwi; Erni Masdupi (Universitas Negeri Padang, 2021)
This study aims to analyze the influence of (1) credit risk, (2) market risk and (3) liquidity risk on return on assets in conventional commercial banks registered in the Financial Services Authority during the COVID-19 pandemic. This study used two moderated variables, namely total of COVID-19 cases and total of COVID-19 death cases. The population in this study is all commercial banks registered in the Financial Services Authority. While the samples in this study were determined by purposive sampling method, that 272 bank samples were obtained in the quarter I –quarter IV of 2020. But the final sample of this study was 244 due to data outliers. The types of data used in this study are secondary data obtained from OJK Publication Report, Indonesian Banking Statistics and JHU CSSE COVID-19 Data. The analysis method used is moderated regression analysis. The results of this study concluded that (1) credit risk negatively and significantly affects the return on assets in conventional commercial banks, (2) market risk has a positive and significant effect on return on assets in conventional commercial banks, (3) liquidity risk has no effect on return on assets in conventional commercial banks, (4) the number of CASES of COVID-19 has no effect on return on assets in conventional commercial banks, (5) the number of COVID-19 death cases shall have no effect on the return on assets of conventional commercial banks, (6) the number of COVID-19 cases does not moderate the influence of credit risk on return on assets in conventional commercial banks, (7) the number of COVID-19 cases strengthens the influence of market risk on return on assets in conventional commercial banks, (8) the number of COVID-19 cases does not moderate the influence of liquidity risk on return on assets in conventional commercial banks, (9) the number of COVID-19 death cases strengthens the influence of credit risk on return on assets in conventional commercial banks, (10) the number of death cases strengthens the influence of market risk on return on assets in conventional commercial banks and (11) the number of death cases does not moderate the influence of liquidity risk on return on assets in conventional commercial banks.